1993
DOI: 10.1007/bf00166860
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature hydrocarbon degradation by Bacillus stearothermophilus from oil-polluted Kuwaiti desert

Abstract: Kuwaiti desert samples contaminated with crude oil contained Bacillus stearothermophilus strains capable of growth on crude oil as a sole source of carbon and energy, obligately at high temperature. No thermophilic oil utilizers were present in water samples collected from the Arabian Gulf. Most of the desert strains had an optimum temperature of 60°C and grew best on pentadecane (C15), hexadecane (C16) and heptadecane (C17). n-Alkanes with shorter and longer chains, n-alkenes, and aromatic hydrocarbons were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(52 citation statements)
references
References 12 publications
0
50
0
2
Order By: Relevance
“…occurring in extreme environments. For example; 368 isolates belonging to the genus Bacillus were isolated from desert samples (Sorkhoh et al, 1993). Two strains (2003) reported Bacillus sp.…”
Section: Isolation Of Diesel-utilizing Bacteriamentioning
confidence: 99%
“…occurring in extreme environments. For example; 368 isolates belonging to the genus Bacillus were isolated from desert samples (Sorkhoh et al, 1993). Two strains (2003) reported Bacillus sp.…”
Section: Isolation Of Diesel-utilizing Bacteriamentioning
confidence: 99%
“…Many of the thermophilic bacterial genera such as Thermomicrobium sp., Bacillus sp., Geobacillus sp., and Thermus sp. were identified and characterized from different hydrocarbon habitats (Sorkhoh et al 1993;Nazina et al 2001;Meintanis et al 2006;Liu et al 2009). Thermus sp.…”
Section: Introductionmentioning
confidence: 99%
“…Many microbial species were used by many researchers to degrade long-chain alkanes like B. stearothermophilus, Acinetobacter sp., B. thermoleovorans, G. kaustophilus, Dietzia sp., B. licheniformis, etc. (Sorkhoh et al 1993;Sakai et al 1994;Kato et al 2001;Sood and Lal 2008;Bihari et al 2010). However, the removal efficiency of the different isolates varied due to their action mechanisms on degradation of pollutants, substrate concentrations and their bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have reported the abilities of bacteria to degrade hydrocarbons with different carbon numbers, most bacteria can use only a narrow range of hydrocarbons. For example, Bacillus stearothermophilus is only capable of growth on C15-C17 (Sorkhoh et al, 1993), Geobacillus jurassicus grows only on C6-C16 (Nazina et al, 2005), and Bacillus thermoleovorans degrades n-alkanes up to C23 . Indeed, few strains capable of degrading a wide range of hydrocarbons have been identified to date.…”
Section: Introductionmentioning
confidence: 99%